Scalings in Linear Programming: Necessary and Sufficient Conditions for Invariance - Pekec, Aleksandar (BRICS Report Series, 1996)
We analyze invariance of the conclusion of optimality for the linear programming problem under scalings (linear, affine, . . . ) of various problem parameters such as: the coefficients of the objective function, the coefficients of the constraint vector, the coefficients of one or more rows (columns) of the constraint matrix. Measurement theory concepts play a central role in our presentation and we explain why such approach is a natural one. Keywords: Sensitivity Analysis, Scaling, Measurement